2008
DOI: 10.1099/ijs.0.2008/000273-0
|View full text |Cite
|
Sign up to set email alerts
|

Photorhabdus temperata subsp. cinerea subsp. nov., isolated from Heterorhabditis nematodes

Abstract: Research and Extension Centre for Fruit Growing, Vadastag 2, H-4244 Ú jfehé rtó , HungaryDuring the characterization of symbiotic bacteria of Hungarian entomopathogenic nematode isolates, a number of bacteria (including strain 3107 T ) isolated from Heterorhabditis downesi and Heterorhabditis megidis showed only moderate 16S rRNA gene sequence similarity to the type strains of all described Photorhabdus species and subspecies. On the basis of the 16S rRNA gene sequence, the phylogenetic relationships of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…Previous studies have suggested that the ITS sequences provide detailed information about variation within and among species of Heterorhabditis (Malan et al, 2008;Nguyen et al, 2008), and gyrB gene sequences are more useful in investigating intrageneric phylogenies of Photorhabdus in contrast to the normally used 16S ribosomal DNA sequences (Akhurst et al, 2004;Tóth and Lakatos, 2008). For phylogenetic analyses in this study, ITS region and gyrB gene were amplified from the genomic DNA of the nematodes and the bacteria, respectively.…”
Section: Pcr Amplification and Cloningmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that the ITS sequences provide detailed information about variation within and among species of Heterorhabditis (Malan et al, 2008;Nguyen et al, 2008), and gyrB gene sequences are more useful in investigating intrageneric phylogenies of Photorhabdus in contrast to the normally used 16S ribosomal DNA sequences (Akhurst et al, 2004;Tóth and Lakatos, 2008). For phylogenetic analyses in this study, ITS region and gyrB gene were amplified from the genomic DNA of the nematodes and the bacteria, respectively.…”
Section: Pcr Amplification and Cloningmentioning
confidence: 99%
“…After removing low quality and vector sequences, the resulting high quality sequences were used to produce alignments of ITS or gyrB with other known nematodes or bacteria (Appendix A) for comparative purposes using ClustalW algorithm (Thompson et al, 1994). For phylogenetic analysis, the unaligned sequence ends were deleted, gaps in the aligned domains were treated as either missing data or a fifth base, and Caenorhabditis elegans and Xenorhabdus nematophila were used as outgroup taxa and to root the trees for Heterorhabditis and Photorhabdus, respectively according to previous studies (Malan et al, 2008;Tóth and Lakatos, 2008). Initially, all our 67 strains were included in phylogenetic analyses using both maximum parsimony (MP) and maximum likelihood (ML) methods.…”
Section: Gene Sequence and Phylogeny Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, chemotaxis studies have shown that, when given a choice, different hosts of X. bovienii prefer either their cognate strain or a strain that comes from a host that is phylogenetically closer to their cognate host The association between Heterorhabditis and Photorhabdus was originally thought to be strictly one-to-one in terms of cospeciation. However, with the increasing number of nematode and bacterial isolates, it has come to light that some Photorhabdus species such as P. temperata (Kuwata, Yoshiga, Yoshida, & Kondo, 2007) (Adams et al, 2006;An & Grewal, 2010;Boemare, 2002;Tóth & Lakatos, 2008). Recently, Maneesakorn et al (2011) investigated coevolutionary relationships between Photorhabdus and Heterorhabditis considering a single gene approach.…”
Section: Entomopathogenic Nematodes-bacteria Cophylogenetic Studiesmentioning
confidence: 98%
“…cinerea 3240 isolated from larvae of the entomopathogenic nematode Heterorhabditis downesi in Hungary. 5 The polysaccharide was obtained by mild acid hydrolysis of the lipopolysaccharide isolated from bacterial cells by the phenol-water procedure. The 1 H NMR and 13 C NMR ( Fig.…”
Section: Andmentioning
confidence: 99%